Macrophage Cell Membrane‐Cloaked Nanoplatforms for Biomedical Applications. Issue 8 (29th June 2022) - Lopes, Joana; Lopes, Daniela; Pereira‐Silva, Miguel; Peixoto, Diana; Veiga, Francisco; Hamblin, Michael R.; Conde, João; Corbo, Claudia; Zare, Ehsan Nazarzadeh; Ashrafizadeh, Milad; Tay, Franklin R.; Chen, Chengshui; et al.
Abstract: Biomimetic approaches utilize natural cell membrane‐derived nanovesicles to camouflage nanoparticles to circumvent some limitations of nanoscale materials. This emergent cell membrane‐coating technology is inspired by naturally occurring intercellular interactions, to efficiently guide nanostructures to the desired locations, thereby increasing both therapeutic efficacy and safety. In addition, the intrinsic biocompatibility of cell membranes allows the crossing of biological barriers and avoids elimination by the immune system. This results in enhanced blood circulation time and lower toxicity in vivo. Macrophages are the major phagocytic cells of the innate immune system. They are equipped with a complex repertoire of surface receptors, enabling them to respond to biological signals, and to exhibit a natural tropism to inflammatory sites and tumorous tissues. Macrophage cell membrane‐functionalized nanosystems are designed to combine the advantages of both macrophages and nanomaterials, improving the ability of those nanosystems to reach target sites. Recent studies have demonstrated the potential of these biomimetic nanosystems for targeted delivery of drugs and imaging agents to tumors, inflammatory, and infected sites. The present review covers the preparation and biomedical applications of macrophage cell membrane‐coated nanosystems. Challenges and future perspectives in the development of these membrane‐coated nanosystems are addressed. Abstract : The aim of this article is to provide an overview of the biomedical applications of macrophage cell membrane‐coated nanoplatforms as next‐generation bioinspired delivery systems for diagnostic, therapeutic, and theranostic purposes in cancer, inflammatory diseases, and infectious ailments. The fabrication of these nanosystems is presented, followed by future perspectives and challenges for their clinical translation.